Alumni Relations Building Blocks to a Successful Strategy - Rincón, Sandra (ICAReAlumni Conference Proceedings, 2021)
ICARe-Alumni 2021 delivered a nanocourse to substitute its annual conference. With the planning committee and trainers, we developed the course to guide participants in developing an engagement strategy in support of their institutional missions. The course comprised of three separate interactive workshops: (1) Building Blocks for a Strategy, (2) Defining Purpose, (3) Developing a Road Map. Each workshop was delivered every two weeks with a separate feedback session which participants could use to ask questions and share their journey. The workshops were delivered on a Tuesday while the feedback sessions on a Friday. The main learning objectives for the workshops were to: 1. Recognize why developing a strategy is important for successful alumni relations and career development programs. 2. Identify and apply the essential building blocks for a strategy to your own organization. 3. Create a roadmap with clear purpose, key performance indicators that align with the needs of the alumni and the institution.